Utility of pre-operative serum thyroid stimulating hormone in predicting thyroid malignancy - K., Arun; K., Santhosh Nayak; Gowda, Suhas (International Surgery Journal, 2017)
Background: Thyroid cancer is the most common endocrine malignancy and its incidence continues to rise. Thyroid carcinoma in most cases presents clinically as a solitary nodule or as a dominant nodule within a multinodular thyroid gland. There are a number of well-established of predictors of malignancy in thyroid nodules. More recently studies have suggested that higher concentration of TSH, even within the normal range are associated with subsequent diagnosis of thyroid cancer in patients with thyroid nodules and even higher serum TSH levels have been found associated with advanced stages of thyroid cancer. The objective of this study was to determine the serum thyroid stimulating hormone (TSH) concentration before surgery in different thyroid malignancies and to compare serum TSH concentration after surgery in thyroid malignancy Methods: A hospital based observational study was conducted in a tertiary care hospital for a period of 2 year. 120 patients presenting with thyroid nodule without an overt thyroid dysfunction during the study period were included in the study. Chi-square was used as test of significance. Independent t test was the test of significance for quantitative data between two groups. Results: Mean serum TSH was higher in thyroid malignancies and significant difference was observed between solitary and multinodular goitre. Mean serum TSH concentrations was significantly high in papillary carcinoma and advanced stages of carcinoma. Mean serum TSH was high in stage III and stage IV (5.17±1.36 mIU/l) compared to stage I and II (4.03±1.87 mIU/l). Conclusions: The study concludes that TSH levels were high in thyroid malignancies arising from multinodular goitre, majority of thyroid malignancies had high levels of serum TSH concentrations and TSH was high with advanced stage of thyroid cancer